Studies Spectroscopic of Water Groups in Hydrates: Exploring the Bonding and Motion of Water Groups in Hydrated Salts (Journal of Advances and Scholarly Researches in Allied Education, 2021)
An introduction to hydrated salts. Beginning with a brief historical introduction to blue vitroyl, the bonding of water groups in a hydrated salt has been explained here. The various modes of motion of water groups with regard to spectroscopic studies have also been described in this chapter. The importance of thermal deaquation and further of deaquation in electric field have been emphasized.